A prospective review of laparoscopic common bile duct exploration with nephroscope and primary closure without T tube - Jolly, H. S.; Veetil, Sreejith Kannummal; Sharma, Binni; Dhingra, Anshul; Jain, Aashima (International Surgery Journal, 2024)
Background: Here we present a pioneering laparoscopic method for common bile duct (CBD) stone management, evaluating its practicality, safety, and effectiveness when employing a nephroscope and omitting the placement of a T tube. Methods: We have prospectively collected data from 100 patients who underwent exclusive CBD laparoscopic CBD exploration (LCBDE) along with/without laparoscopic cholecystectomy diagnosed to have Cholelithiasis with choledocholithiasis with a radiological CBD diameter of 10mm or more. Mortality, morbidity, hospital stay, and average duration of hospital stay were all assessed. Results: In this prospective series 100 patients underwent the procedure, of which we had no mortality, of the 100 patients, 4 patients (4%) had bile leak i.e., bile output of more than 100 ml n drain, and 2 patients (2%) needed endoscopic retrograde cholangiopancreatography (ERCP) and stenting. The other 2 patient’s leak settled by itself without any interventions. One patient (1%) was diagnosed to have sepsis post LCBDE which also required a prolonged stay of 7 days for antibiotics. Conclusions: LCBDE offers good clinical outcomes in dealing with CBD stones. Surgeons experienced in laparoscopy can perform this procedure securely and efficiently.